Physical Characteristics of Entrance Areas of Coss Passage alongside Jl. Agro, Yogyakarta - Yurista Hardika Dinata; Djoko Wijono (Built Environment Studies, 2020)
This study aimed to determine the physical characteristics of the entrance areas of cross passage alongside Jl. Agro, Yogyakarta. This study was a descriptive qualitative research, where the observational cases were determined based on the purposive sampling technique. The research results showed that commercial buildings with a short seatback constructed the wall space around the entrance areas of cross passage. The scale of the road space was formed by a combination of balanced and narrow space affected by the height of the building. Street floor space, signage, and vegetation showed different patterns at each entrance areas of cross passage. As part of street furniture, gate and sculpture turned into a strong identity in the cross-passage area. There were nine entrance areas of cross passage as a case of observation. The nine cases' physical appearance showed the distinctive form of the archipelago and local identity as three different elements bound them: urban village area as a local identity, Mataram ditch as a heritage of the agricultural system, and universities as a generator of activity.